The role of home environment, motivation and reading in the learning of english as a second language: a study involving the part two students of UiTM Terengganu / Rozlan Abdul Rahim, Gopala Krishnan Sekharan Nair & Rasaya Marimuthu - Abdul Rahim, Rozlan; Sekharan Nair, Gopala Krishnan; Marimuthu, Rasaya (2008)
The weakness in the command of the English language among graduates produced by local universities including UiTM is a cause for concern at all levels. Handicap in the English language, which often started at their primary and secondary level can be attributed to several factors, i.e. motivation, or rather the lack of it, an adverse home environment, lack of parental encouragement, the family socio-economic status, and also the lack of exposure to the English language itself. In view of this, the researchers had intended to find out if there were any significant relationships among the factors mentioned above to their motivational orientations with regards to the students’ achievement in the English Language. 244 Part Two students who had enrolled for the BEL200 Mainstream English I course were selected as respondents for this study, using the convenience sampling method. A questionnaire was administered to the respondents to gauge the role played the factors mentioned above, while Gardner and Lambert’s AMT Battery was used to gauge their motivational levels and orientation. An English Language achievement test was also conducted on the students. The findings showed that there were significant positive relationships between the factors mentioned above and the respondents’ motivational orientation. Interestingly, it was also found that reading habits can boost the achievement level in the English Language irrespective of their motivational level and orientation. However, a positive relationship was not evident between exposure to the language and the respondents’ motivational orientation. It was also evidently proven that the quantity of reading done by the respondents was not a reliable predictor of their English Language achievement. In fact, home environment was found to be a better predictor towards this cause. The researchers wish to reiterate the findings of this study that students’ motivation (both instrumental and integrative) towards the English Language need to be exploited in as many ways as possible to enable them to become more proficient in the English Language, and that everyone has a role to play towards this end.